Inorganic-organic hybrid materials based on functionalized silica and carbon: a comprehensive understanding toward the structural property and catalytic activity difference over mesoporous silica and carbon supports - Bordoloi, Ankur; Mathew, Nevin T.; Lefebvre, F.; Halligudi, Shivaraj B. (Microporous and Mesoporous Materials, 2008)
Inorganic-organic hybrid materials based on functionalized silica and carbon were synthesized by anchoring molybdovanadophosphoric acid (H-5[PMo10V2O40]center dot 32.5H(2)O) onto amine-functionalized SBA-15, ethane-bridged SBA-15 and mesoporous carbon, respectively. Small angle X-ray diffraction, N-2 sorption analysis, HRTEM, SEM, IFT-IR, CP-MAS NMR were used to diagnose the mesoporous structure of inorganic-organic hybrid materials. The structural integrity of molybdovanadophosphoric acid has been found to be retained after immobilization over mesoporous materials. These inorganic-organic hybrid materials were tested in the environmentally friendly oxidation of 2-methylnaphthalene (2MN) with 30%, aqueous hydrogen peroxide. Molybdovanadophosphoric acid containing mesoporous organosilica hybrid material (ethane-bridged SBA-15) exhibited higher catalytic activities in the oxidation of 2MN to give a clean product 2-methy-1,4-naphthoquinone (menadione vitamin K3 precursor), because of the improved hydrophobicity of the material. The correlation between structural properties and catalytic activities of these hybrid materials has been well addressed in our present studies. (c) 2008 Elsevier Inc. All rights reserved.
Keywords: 2-Methylnaphthalene; inorganic-organic hybrid materials; mesoporous carbon; mesoporous organosilica; Oxidation

In-situ experimental and computational approach to investigate the nature of active site in low-temperature CO-PROX over CuOx-CeO2 catalyst - Adak, Shubhadeep; Rabeah, Jabor; Ranjan, Ravi; Khan, Tuhin Suvra; Poddar, Mukesh Kumar; Gupta, Rishi Kumar; Sasaki, Takehiko; Kumar, Sagar; Bordoloi, Ankur; Gopinath, Chinnakonda S.; Bruckner, Angelika; Bal, Rajaram (Applied Catalysis A-General, 2021)
Preferential oxidation (PROX) of carbon monoxide (CO) in presence of excess hydrogen is a necessity to prevent poisoning of the Pt-anode by CO in PEMFCs (Polymer Electrolyte Membrane Fuel Cell). A highly active catalyst, 5 wt% Cu-CeO2 showed 100 % CO conversion at 65 degrees C without any undesirable oxidation of H-2. The catalyst showed no deactivation even after 100 h on stream, making it viable for practical fuel cell application. Operando EPR in the PROX reaction condition revealed highly dispersed mixed valent cations with oxygen vacancies, responsible for the low-temperature PROX activity. At the active site, both Cu and Ce ions were shown to reversibly change their valence states to facilitate the abstraction of bridging lattice oxygen for CO oxidation to CO2. This surface oxygen mediated CO oxidation was found to be much faster than that of H-2 to H2O, which could explain the complete selectivity of oxygen for CO2 formation.
Keywords: CuOx-CeO2; interface; Oxygen vacancy; PROX; Synergistic